The colonial educational violence in Algeria - ABBACI , Madjid (The Algerian Historical Journal, 2026)
The instrumentalization of the school and by expansion of the educational system as a means of domination during the colonial period is, as little as we can say, a colonial reality whose aim is to perpetuate domination and to rule out all specter of revolt or rebellion. By the invention of a national novel, a new identity and by the illusion of integration into a new Eurocentric whole, towards a modernity with civic, universal and human values. A thesis that invalidates a “rebellious”, “terrorist” Algeria conscious of its own novel and its identity in the Zaouia and other Islamic centers.